2009
DOI: 10.2528/pier09010803
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Analysis of a Non Invasive Microwave Radiometry Imaging System Emphasizing on the Focusing Sensitivity Optimization

Abstract: Abstract-A Green's function based methodology has been developed and implemented with the view to optimize the focusing properties and thus the performance of a Microwave Radiometry Imaging System (MiRaIS). The system consists of an ellipsoidal conductive wall cavity and a sensitive radiometric receiver and its operation principal is based on the convergence of the radiation from one focal point, where the subject or phantom is placed, on the other, where the receiver antenna is positioned. A two-layered cylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In order to solve this problem, a Green's function technique is adopted [1,16,17]. According to the Reciprocity theorem, a response of a system to a source is unchanged when source and measurer are interchanged.…”
Section: Theoretical Electromagnetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In order to solve this problem, a Green's function technique is adopted [1,16,17]. According to the Reciprocity theorem, a response of a system to a source is unchanged when source and measurer are interchanged.…”
Section: Theoretical Electromagnetic Analysismentioning
confidence: 99%
“…Towards the enhancement of the system's focusing properties, in previous recent work carried out by our group, various setups have been investigated aiming to improve the transition of the diffraction index from air to the head and vice versa. Specifically, initially the receiving antenna was covered by two layers of different dielectric properties, then a thin lossless dielectric layer was placed on the surface of the human head model [1] and various configurations using lossless dielectric materials placed around the head models/phantoms or used as filling material inside the ellipsoidal cavity were also implemented [4,5]. With appropriate adaptation of values of the dielectric properties and the thicknesses of each layer, a stepped change of the refraction index on the scattering objects-air interface has been achieved, hence a better radiation focusing inside the brain has been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method the regularized solution was obtained using a parameterized trust region approach to estimate the region of maximum curvature of the L-curve. Method proposed here can be used in other imaging techniques [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave radiometry was proposed approximately 30 years ago to be used as a diagnostic imaging method to noninvasively measure temperature distributions inside the human body. Since then numerous research results have been reported regarding the clinical practical value of this passive imaging methodology which exhibits unique capabilities [7,8]. The applications of microwave radiometry in clinical medicine aim mainly at obtaining information about internal in-depth body temperature patterns by the non-traumatic measurement of natural thermal radiation from body tissues at low microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%